The Effect of Capital Intensity, Sales Growth and Gender Diversity on Tax Avoidance: An Empirical Study of Companies Listed on the Indonesia Stock Exchange - Dayanti, Anggun Dwi; Fitriyani, Yuniar; Andarsari, Pipit Rosita (Manajemen Multitalenta Indonesia, 2025)
This research investigates how capital intensity, sales growth, and gender diversity impact tax avoidance. The study focuses on food and beverage companies listed on the Indonesia Stock Exchange during the 2022–2023 period. Using purposive sampling, 42 companies were selected for analysis. Data were analyzed with SPSS version 26, employing multiple linear regression techniques. The findings reveal that sales growth significantly influences tax avoidance, whereas capital intensity and gender diversity do not exhibit a significant effect.